Implementation of English Language Teaching (ELT) Through Understanding Non-EFL Students’ Learning Styles - Nur Fitria, Tira (Universitas Nahdatul Ulama Surabaya, 2023)
This research investigates the non-EFL students9 learning styles and describes how to teachEnglish with different learning styles. This research is descriptive qualitative research. The analysisshows that are six types of students9 learning styles including VAK (Visual, Auditory, and Kinesthetic),also the combinations of learning styles including visual-auditory, visual kinesthetic, and auditorykinesthetic. This also shows that students can have more than one learning style such as visual-auditory,visual-kinesthetic, and auditory-kinesthetic learning styles. Non-EFL students learning a language tendto apply a visual learning style. Students with a visual learning style more easily absorb informationfrom the sense of sight, such as through pictures/images. While students with an auditory learning styleeasily understand when processing information through the sense of hearing (listening). On the otherhand, students with a kinesthetic learning style need opportunities to be actively moving. Therefore, withunderstanding and the teacher’s knowledge of learning styles each student in the teacher’s class canimplement interesting and meaningful English learning. Understanding the learning styles may be veryhelpful for students to learn via activities in the manner in which they learn best. It will assist students tocomprehend the course material easily, so enhancing their motivation and language skills, enhancingtheir enjoyment of the learning process, reducing their stress levels, and resulting in higher performance.When the teacher understands students’ learning styles, teachers should provide interesting materials andan appropriate learning environment